2003
DOI: 10.1063/1.1570505
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high magnetic fields on the morphology of soft magnetic α′-FeN films

Abstract: The effect of high magnetic field on the microstructure and magnetic properties of α′-FeN films has been studied. The application of a high magnetic field during sputter deposition has a significant influence on the microstructure of α′-FeN films. In particular, the grain growth and the surface roughness are suppressed, and concurrently the coercivity becomes much lower. α′-FeN films deposited in magnetic fields of 2 and 4 T exhibit smooth surfaces with root-mean-square (rms) roughness of, respectively, 0.38–1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The saturation magnetization gradually increases as the increase of the magnetic flux density. In some studies [11,12], it has already been confirmed that the saturation magnetization can increase with the application of magnetic field. Especially in the case of Fe 3 O 4 thin films, 1 T field increases the saturation magnetization for 150%-200% [13].…”
Section: Resultsmentioning
confidence: 82%
“…The saturation magnetization gradually increases as the increase of the magnetic flux density. In some studies [11,12], it has already been confirmed that the saturation magnetization can increase with the application of magnetic field. Especially in the case of Fe 3 O 4 thin films, 1 T field increases the saturation magnetization for 150%-200% [13].…”
Section: Resultsmentioning
confidence: 82%
“…At present, there is no empirical agreement on the mechanism of the uniaxial anisotropy, because the applicability of the models above is strongly dependent of the sample preparation methods. Wang et al found that the application of a high magnetic field during sputtering deposition has a significant influence on the microstructure of the magnetic film [14]. Therefore, we compared the typical x-ray diffraction patterns of the multilayers, which were fabricated with and without an external inplane field of 200 Oe.…”
Section: Resultsmentioning
confidence: 99%
“…and the effects of magnetic field on microstructures have been studied [14]. In our previous study, we have found that the grain growth of FeN films is suppressed by applying a high magnetic field during film deposition [15] and theL1 0 ordering process in FePt films is enhanced by applying a magnetic field during postdeposition annealing [16]. In this study, we investigate the influence of magnetic field annealing on the coercivity and grain size of the FePt films.…”
Section: Introductionmentioning
confidence: 97%